Dabsyl chloride derivatisation of melamine followed by high-performance liquid chromatography determination in water samples. Issue 15 (7th December 2016) - Faraji, Mohammad; Amini Kadijani, Parisa
ABSTRACT: A new and sensitive precolumn derivatisation with dabsyl chloride was developed for the analysis of melamine in water samples by high-performance liquid chromatography (HPLC) with visible detection. Derivatisation with dabsyl chloride leads to improving sensitivity and hydrophobicity of melamine. Under optimum conditions of derivatisation and microextraction, the method yielded a linear calibration curve ranging from 10 to 2000 µg L −1 with a determination coefficient (R 2 ) of 0.9952. Limit of detection (LOD) and limit of quantification (LOQ) were 2.0 and 6.0 µg L −1, respectively. The relative standard deviation per cent (RSD%) for intraday and inter-day extraction and determination at 20 and 200 µg L −1 levels of melamine was less than 8.2% ( n  = 6). Finally, the proposed method was successfully applied for the determination of melamine in different water samples and satisfactory results were obtained (relative recovery ≥91%).